2020
DOI: 10.3390/coatings10020182
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Doped Titanium Dioxide Nanoparticles As Potential Scaffold for Hydrazine Chemical Sensor Applications

Abstract: Herein, we report the fabrication of a modified glassy carbon electrode (GCE) with high-performance hydrazine sensor based on Fe-doped TiO 2 nanoparticles prepared via a facile and low-cost hydrothermal method. The structural morphology, crystalline, crystallite size, vibrational and scattering properties were examined through different characterization techniques, including FESEM, XRD, FTIR, UV-Vis, Raman and photoluminescence spectroscopy. FESEM analysis revealed the high-density synthesis of Fe-doped TiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In Raman spectra, four main peaks were observed at 145 cm −1 , 396 cm −1 , 514 cm −1 , and 637 cm −1, which belong to Eg, B1g, A1g + B1g, Eg mode, respectively. The main peaks observed in Raman spectra were well correlated to earlier reports confirms the phase of the prepared samples [20,33]. The position of the main peak at 145 cm −1 is slightly shifted towards a higher wavenumber when Fe was doped in TiO 2 .…”
Section: Structural Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…In Raman spectra, four main peaks were observed at 145 cm −1 , 396 cm −1 , 514 cm −1 , and 637 cm −1, which belong to Eg, B1g, A1g + B1g, Eg mode, respectively. The main peaks observed in Raman spectra were well correlated to earlier reports confirms the phase of the prepared samples [20,33]. The position of the main peak at 145 cm −1 is slightly shifted towards a higher wavenumber when Fe was doped in TiO 2 .…”
Section: Structural Analysissupporting
confidence: 89%
“…Rodriguez and co-workers [19] used the sol-gel technique for the synthesis of Fe-incorporated TiO 2 and observed a decrease in the optical bandgap from 3.3 eV to 2.9 eV with enhanced absorption in the visible region as the incorporating concentration of Fe increases. Fe-doped TiO 2 NPs prepared by the hydrothermal method were applied as an efficient electron mediator for the fabrication of hydrazine chemical sensor using glassy carbon electrode [20] which proves to be a sensitive sensor. The sol-gel routed spin coating technique was employed to synthesize Fe-doped TiO 2 NPs and observed that the optical transmittance is was decreased with increasing Fe dopant concentrations [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to “Inorganic crystal structure database (ICSD) reference No. 01-080-1268”, the peaks found at 29.42°, 32.53°, 35.5°, 38.7°, 48.6°, 53.51°, 58.29°, 61.51°, 66.17°, and 68.07° corresponded to (210), (110), (002), (111), (−202), (020), (202), (−113), (−311), and (220) planes in the monoclinic structure of CuO [ 38 , 39 , 40 ]. The sharpness of the peaks indicated that pure CuO was highly crystalline.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of CHCl 3 on the oxygenated ZnO reduces its bandgap, and the deposition of O on a ZnO nanocluster increases its sensitivity to CHCl 3 and may facilitate CHCl 3 removal or detection. Another facile, low-cost hydrothermal method was used by Umar et al [14] for the synthesis of Fe-doped TiO 2 nanoparticles. These nanoparticles were used to prepare modified glassy carbon electrodes (GCE) for the development of a hydrazine sensor.…”
Section: This Special Issuementioning
confidence: 99%